2020
DOI: 10.3389/fncel.2020.564081
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Optical Quantal Analysis of Miniature Events Reveals Enhanced Frequency Following Amyloid β Exposure

Abstract: Non-evoked miniature release of neurotransmitters is increasingly recognized as playing an important role in neural function and is implicated in synaptic plasticity, metaplasticity, and homeostasis. Spontaneous miniature release events (minis) are usually measured electrophysiologically by recording the miniature postsynaptic currents (mEPSCs) that they evoke. However, this indirect technique can be confounded by changes within the postsynaptic neuron. Here, using the fluorescent probe SynaptopHluorin 2×, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 62 publications
(87 reference statements)
1
1
0
Order By: Relevance
“…Using pharmacological and optogenetic approaches in cultured brain slices, we confirmed that repeated administration of an NMDAR-dependent low frequency stimulation LTD induction protocol that is based on one used in physiological plasticity studies (but delivered in excess) indeed drives phosphorylation of endogenous tau at pathology-associated residues. We further implicated Aβ-induced increases in presynaptic probability of neurotransmitter release, which have been reported by us and others previously [ 126–128 ] in generating the low-frequency synaptic activity required to induce LTD [ 129 ]. This study provides evidence for a direct mechanistic link between the two key proteins of AD ( Figure 2 ) and suggests that LTD-associated proteins might constitute potential therapeutic targets.…”
Section: Intersection Of Amyloid and Tau – Dysfunction At The Synapsesupporting
confidence: 67%
“…Using pharmacological and optogenetic approaches in cultured brain slices, we confirmed that repeated administration of an NMDAR-dependent low frequency stimulation LTD induction protocol that is based on one used in physiological plasticity studies (but delivered in excess) indeed drives phosphorylation of endogenous tau at pathology-associated residues. We further implicated Aβ-induced increases in presynaptic probability of neurotransmitter release, which have been reported by us and others previously [ 126–128 ] in generating the low-frequency synaptic activity required to induce LTD [ 129 ]. This study provides evidence for a direct mechanistic link between the two key proteins of AD ( Figure 2 ) and suggests that LTD-associated proteins might constitute potential therapeutic targets.…”
Section: Intersection Of Amyloid and Tau – Dysfunction At The Synapsesupporting
confidence: 67%
“…While this account of AD pathogenesis is highly consistent with existing experimental data obtained in a variety of model systems and with clinical observations, there is an alternative possible interpretation of the current evidence. It remains possible that postsynaptic weakening is a primary event, possibly the result of pathological signalling downstream of postsynaptic binding of pathogenic conformations of Aβ (Um et al, 2012;Kim et al, 2013), and this engages mechanisms of HSP to enhance presynaptic function and thereby synaptic activity in order to preserve synaptic strength (Taylor et al, 2020). Although this view seems much less favoured by the available evidence, it would again place HSP in an important role in pathogenesis, albeit as a maladaptive response to a pathological insult rather than as a primary, upstream event.…”
Section: Alzheimer's Diseasementioning
confidence: 99%